Perancangan Identitas Visual Serta Media Promosi Dapur Yura - Wiguna, I Putu Agus Jaya; Dinata, Ramanda Dimas Surya; Rimbawan, Ari; Lestari, Ni Putu Emilika Budi; Setyawan, Agus Budi (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
Dapur Yura is a Micro, Small, and Medium Enterprise (MSME) engaged in the Indonesian culinary sector. This MSME serves various typical Indonesian menus, such as yellow rice, geprek chicken, fresh vegetables, and tumpeng rice, which are made with quality ingredients and authentic flavors. Founded by Pipin Swandewi in 2023, Dapur Yura is located at Jalan Raya Baturiti No. 99, Batunya, Baturiti District, Tabanan Regency, Bali. Currently, Dapur Yura does not have a strong visual identity to reflect the characteristics of its products. In addition, the available promotional media is still limited, so it has not been able to reach a wider market. This design aims to create a visual identity, such as a logo and Graphic Standard Manual (GSM), which can increase brand awareness. In addition, a marketing strategy is also designed through offline promotional media, such as signboards, banners, and business cards, as well as online media in the form of Instagram content. This study uses observation methods and direct interviews with MSME owners, as well as a SWOT analysis to identify business strengths, weaknesses, opportunities, and threats. With this design, Dapur Yura is expected to increase sales, expand market segmentation, and become better known to the public.